ORIGIN OF CHONDRITIC FORSTERITE GRAINS - Pack A.; Palme H.; Shelley J.M.G. (My University, 2005)
Iron-poor and refractory lithophile element (RLE) rich forsterite grains occur in all major types of unequilibrated chondrites. In our laser ablation inductively coupled mass spectrometry (LA-ICPMS) minor and trace element study we show that refractory forsterites (RF) from carbonaceous (CC), unequilibrated ordinary (UOC) and a Rumuruti chondrite (RC) have similar chemical compositions with high RLE concentrations and low concentrations of Mn, Fe, Co and Ni. Fractionation of RLEs and rare earth elements (REEs) is in agreement with formation by crystallization from a RLE rich silicate melt. Low concentrations and the fractionation of moderately siderophile elements (Fe, Co, Ni) in RFs suggests formation at low oxygen fugacity, possibly in equilibrium with primitive Fe,Ni metal condensates in a gas of solar composition. Anomalously high Ti in the parental melt can be explained by Ti3+/Ti4+ ∼1.5, supporting formation of RF in highly reducing conditions. Low Mn concentrations indicate formation at high temperatures (>∼1160 K). The model of formation of RFs and the accompanying physico-chemical conditions during their formation as well as their relation to non refractory olivine are discussed.
Keywords: forsterite; chondrites